Opóźnienie rozwoju języka a ryzyko dysleksji rozwojowej - Jastrzębowska, Grażyna (Logopedia Silesiana, 2012)
Slower language development versus a risk of developmental dyslexia The author’s research focuses on specific speech and language disorders. Then, she pays attention to main difficulties and reasons of this phenomenon as well as relation between any developmental disorders, in particular developmental dyslexia. The main aim of the article is to show the research results in the area of dependency between developmental dyslexia and a low level of language abilities. The author answers two main questions. First of all, she wants to find an answer if each child with speech disorder is endangered with developmental dyslexia, and then, if a speed of speech development among all children with mental deficit belonging to a dyslexia risk group is shown. The results of the conducted research show the existing relation between children with speech disorder and a speed of language development. What is more, the author presents a closer correlation between slower language acquisition and dyslexia than in the opposite direction. In the case of the second group of children it is claimed that those children who are endangered by dyslexia had some problems with language acquisition in the past.